Pengembangan Usaha Kelompok Peternak Lebah Trigona Ampel Mesari Banjar Bebali Desa Berembeng - Wijaya, I Gusti Ngurah Satria; Ciptahadi, Ketut Gus Oka; Ayuningsih, Ni Putu Meina; Narindro, Laser (STMIK Royal, 2023)
Abstract: The Trigona Beekeepers Group